Characterization of clinically-attenuated Burkholderia mallei by whole genome sequencing: candidate strain for exclusion from Select Agent lists. - Steven E Schutzer; Linda R K Schlater; Catherine M Ronning; David DeShazer; Benjamin J Luft; John J Dunn; Jacques Ravel; Claire M Fraser-Liggett; William C Nierman (PLoS ONE)
Background Burkholderia mallei is an understudied biothreat agent responsible for glanders which can be lethal in humans and animals. Research with this pathogen has been hampered in part by constraints of Select Agent regulations for safety reasons. Whole genomic sequencing (WGS) is an apt approach to characterize newly discovered or poorly understood microbial pathogens. Methodology/principal findings We performed WGS on a strain of B. mallei, SAVP1, previously pathogenic, that was experimentally infected in 6 equids (4 ponies, 1 mule, 1 donkey), natural hosts, for purposes of producing antibodies. Multiple high inocula were used in some cases. Unexpectedly SAVP1 appeared to be avirulent in the ponies and mule, and attenuated in the donkey, but induced antibodies. We determined the genome sequence of SAVP1 and compared it to a strain that was virulent in horses and a human. In comparison, this phenotypic avirulent SAVP1 strain was missing multiple genes including all the animal type III secretory system (T3SS) complex of genes demonstrated to be essential for virulence in mice and hamster models. The loss of these genes in the SAVP1 strain appears to be the consequence of a multiple gene deletion across insertion sequence (IS) elements in the B. mallei genome. Therefore, the strain by itself is unlikely to revert naturally to its virulent phenotype. There were other genes present in one strain and not the other and vice-versa. Conclusion/significance The discovery that this strain of B. mallei was both avirulent in the natural host ponies, and did not possess T3SS associated genes may be fortuitous to advance biodefense research. The deleted virulence-essential T3SS is not likely to be re-acquired naturally. These findings may provide a basis for exclusion of SAVP1 from the Select Agent regulation or at least discussion of what else would be required for exclusion. This exclusion could accelerate research by investigators not possessing BSL-3 facilities and facilitate the production of reagents such as antibodies without the restraints of Select Agent regulation.